2018
DOI: 10.1021/acs.est.7b06407
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Electrochemical Ceramic Membrane Filtration System for Efficient Contaminant Removal from Waters

Abstract: Inability to remove low-molecular-weight anthropogenic contaminants is a critical issue in low-pressure membrane filtration processes for water treatment. In this work, a novel electrochemical ceramic membrane filtration (ECMF) system using TiO@SnO-Sb anode was developed for removing persistent p-chloroaniline (PCA). Results showed that the ECMF system achieved efficient removal of PCA from contaminated waters. At a charging voltage of 3 V, the PCA removal rate of TiO@SnO-Sb ECMF system under flow-through mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(48 citation statements)
references
References 69 publications
0
48
0
Order By: Relevance
“…An electric field is usually applied crosswise to the membrane employing electrodes on both sides of the membrane. The electric field can also be applied between the membrane and other electrode, or in the case of a ceramic membrane, it may serve as an electrode itself [40,57]. Membrane flux is directly proportional to the applied electrical field strength [38,40,58].…”
Section: Electric Fieldmentioning
confidence: 99%
“…An electric field is usually applied crosswise to the membrane employing electrodes on both sides of the membrane. The electric field can also be applied between the membrane and other electrode, or in the case of a ceramic membrane, it may serve as an electrode itself [40,57]. Membrane flux is directly proportional to the applied electrical field strength [38,40,58].…”
Section: Electric Fieldmentioning
confidence: 99%
“…solution processing [48,[102][103][104][105]. Using a microfluidic approach, Bacchin et al showed how a small change in surface properties of a poly-dimethylsiloxane (PDMS) has drastic consequences on pore blocking and particle adsorption [59].…”
Section: Membrane Adsorption and Pore Blockingmentioning
confidence: 99%
“…The spatial effects could be regulated by changing the pore morphology (Xiao et al, 2014a;Fan et al, 2018), surface roughness (Hashino et al, 2011;Feng et al, 2017), and surface topography of the membrane (e.g., prism/pyramid/embossing-patterned membranes Won et al, 2016 and hierarchically textured membranes Zhao et al, 2018). In addition, electrocatalytic membranes have been developed to produce reactive species (such as hydroxyl radicals) on the membrane surface in situ, thus breaking the membrane-foulant interactions (Yang Y. et al, 2011;Yang et al, 2012;Zheng et al, 2018).…”
Section: Membrane Modification For Tuning the Membrane-foulant Interamentioning
confidence: 99%